Euthanasia in Malaysia: Opinions and controversies - Md Arif, Asma'; Jeyasingam, Vaishnavi; Chan, Lucy (Faculty of Medicine, University of Malaya, 2002)
Euthanasia is one of the most controversial topics of the 2]" century after cloning and genetic engineering. Has this issue arisen now due to changes in attitude and perception on life of the modem society' This project was undertaken to study the opinions of 2 selected groups of people and secondly, to highlight the legal, ethical and religious controversies on euthanasia. Two groups comprising medical undergraduates and medical personnel were given a questionnaire pertaining 10 his{her opinion and altitude towards euthanasia. The second part of the project was conducted via interviews. The overall opinion from 399 respondents showed that 67.91% are against the practice of euthanasia. Religion is a powerful force against it as Malaysians in general are God-fearing people. There should be proper guidelines explaining how a doctor should respond to patients or family members of patients who request for euthanasia to be performed. It is not legal in Malaysia, but the court has the inherent power to permit it should a particular case have substantial reasoning and evidence. In conclusion, the level of awareness on euthanasia among medical staff and undergraduates is satisfactory. However, most of them do not approve euthanasia in Malaysia.